Experimental Investigation of the Effect on Surface Roughness of Cutting Tool Coating and Cutting Parameters on CNC Milling of AA7475-T7351 and AA2219-T7351 Alloys - İrizalp, Simge; Karaoğlu, Handenur; Erçayhan, Yiğit; Akgün, Selda (Fırat University, 2024)
In this study, cutting speed (500, 600, 700 m/min), feed (0.1 and 0.15 mm/tooth), and depth of cut (1 and 8 mm) were used as parameters in the machining of AA2219-T851 and AA7475-T7351 alloys, and the effects of cutting parameters on surface roughness were investigated by using uncoated WC cutting tool and ZrN coated cutting tool. The surface roughness of the machined surfaces was investigated by surface profilometer. As a result of the machining operations, the cutting speed, feed, depth of cut, and cutting tool were determined at which the optimum surface quality was obtained. As a result, the surface results of two aluminum alloys that have different strengths were compared, and optimum machining parameters were found. The lowest surface roughness was obtained at 700 mm/min cutting speed, 0.1 mm/tooth, and 1 mm feed parameters, and as the feed rate increased, the surface quality increased and better surface properties were achieved by using ZrN-coated cutting tool.

Bu çalışmada AA 2219-T851 ve AA 7475-T7351 alaşımlarının frezelenmesinde kesme hızı (500, 600, 700m/dk), ilerleme miktarı (0,1 ve 0,15 mm/diş) ve talaş derinliği (1 ve 8 mm) değişkenleri kullanılmış ve kaplamasız tungsten karbür (WC) kesici uç ve zirkanyum nitrür (ZrN) kaplamalı kesici uç kullanılarak kesme parametrelerinin yüzey pürüzlülüğü üzerindeki etkileri incelenmiştir. Deneyler sonucunda en ideal yüzey kalitesinin elde edildiği kesme hızı, ilerleme miktarı, talaş derinliği ve kesici uç belirlenmiştir. Sonuç olarak, iki farklı mekanik dayanıma sahip alüminyum alaşımının yüzey sonuçları karşılaştırılıp optimum işleme değerleri bulunmuştur. En düşük yüzey pürüzlülüğü 700 mm/dk kesme hızı, 0,1 mm/diş ve 1 mm ilerleme miktarı parametrelerinde elde edilmiş ve ilerleme hızı arttıkça yüzey kalitesinin artmasının yanında ZrN kaplamalı kesici uç kullanılması ile daha iyi yüzey özelliklerine ulaşılmıştır.
AA7475-T7351 ve AA2219-T851 Alaşımlarının Frezelenmesinde Kesici Takım Kaplamalarının ve Kesme Parametrelerinin Yüzey Pürüzlülüğü Üzerine Etkisinin Deneysel Olarak İncelenmesi
Keywords: Material Design and Behaviors; Malzeme Tasarım ve Davranışları